The Role of Functional and Emotional Value Co-Creation Within Sharing Economy Platforms on Repurchase Intention - Suryawardana, Edy; Dyah Pitaloka, Dynda Aisyah; Soelistiyono, Anitiyo; Richadyanato, Richadyanato (Integrated Journal of Business and Economics (IJBE), 2024)
Repurchase Intention is part of consumer behaviour that aspires for repeat purchases on the products or services of an organization. Consumers begin with a consideration on the necessities to purchase. Continuing this, consumers then decided on how many products will be purchases. The aim of this paper is to investigate and examine the role of functional and emotional value creation in the relationship between customer ethical perceptions and social support sharing economy platform with repurchase intention. This paper selects 402 consumers using sharing economy platforms in Indonesia and tests the regression relationships of the five constructs using Structural Equation Model with the AMOS 24.00 tool. This finding indicates that social support and consumer ethical perception showed an important antecedent towards Functional Value Co-Creation and Emotional Value Co-Creation and that the two has a positive impact of Repurchase Intention. This suggests that Functional Value Co-Creation and Emotional Value Co-Creation possess an important role as a mediator between social support and consumer ethics perception with Repurchase Intention. With a literature review related to consumer behaviour, consumer ethics, value co-creation, and sharing economy platforms, this paper proposes a unique analysis on the relationship roadmap for customer participation and consumer ethics with Repurchase Intention